A Lucky Case of Successful Free Fibula Osteocutaneous Flap Harvest in Peronea Arteria Magna - Rosli, Mohamad Aizat; Wan Sulaiman, Wan Azman; Halim, Ahmad Sukari (Archives of Plastic Surgery, 2022)
The free fibula flap (FFF) is based on the peroneal artery (PA) system, and it is well known that several anatomical variations of the lower limb vascular system exist, including peronea arteria magna (PAM). PAM is a rare congenital variation in which both anterior tibial artery and posterior tibial artery are either aplastic or hypoplastic, and as a result, PA will be the dominant blood supply to the foot. This variation was described as type III-C in Kim-Lippert's Classification of the Infra-Popliteal Arterial Branching Variations. The awareness of its existence is crucial as it often precludes FFF from being harvested due to the risk of significant limb ischemia and limb loss. Despite some literature reporting donor site complications and impending limb loss following FFF harvest in PAM, preoperative vascular mapping before FFF transfer remains controversial among the microsurgeons. We present a case with an incidental intraoperative finding of PAM that had a successful FFF harvest by luck, without preoperative vascular mapping.
Keywords: fibula; free tissue flaps; tibial arteries; lower extremity; foot